Key drivers of the future European printed packaging market - Horváth Csaba; Koltai László; Orgován Katalin (Inovacijos Leidybos, Poligrafijos ir Multimedijos Technologijose)
Europe’s packaging sector is transforming—driven by innovation, regulation, and collaboration. The sector continues to grow while undergoing significant change, responding to increasingly complex expectations from regulators, brand owners, and consumers alike. Drawing on recent conference presentations, journal articles and market reports, the authors present detailed the key drivers of the packaging market: sustainability and regulation, the growth of e-commerce, changing consumer attitudes and lifestyles, digitalisation and innovation, advances of printing technology and packaging format innovation.